2011
DOI: 10.1042/bc20100067
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CtBP family protein isoforms in breast cancer and their role in chemoresistance

Abstract: Background information. CtBPs [C-terminal (of E1A) binding protein] have roles in the nucleus as transcriptional co-repressors, and in the cytoplasm in the maintenance of vesicular membranes. CtBPs are expressed from two genes, CTBP1 and CTBP2, mRNA products of which are alternatively spliced at their 5′-ends to generate distinct protein isoforms. Extensive molecular and cellular analyses have identified CtBPs as regulators of pathways critical for tumour initiation, progression and response to therapy. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 45 publications
(92 reference statements)
5
48
1
Order By: Relevance
“…CHIP protein is decreased in human breast cancer tissues and is inversely correlated with their malignancy [21]. The physiological relevance of CHIP and CtBP2 to the pathogenesis of human breast cancer has never been addressed, but our present study implies that the elevated CtBP2 observed in human breast cancer [12] may be due to inefficient regulation caused by low levels of CHIP protein and may contribute to the anti-apoptotic property of human breast cancer by repressing pro-apoptotic gene expression.…”
Section: Regulation Of Ctbp2 By Chip Affects the Expression Of Ctbp2 mentioning
confidence: 53%
See 2 more Smart Citations
“…CHIP protein is decreased in human breast cancer tissues and is inversely correlated with their malignancy [21]. The physiological relevance of CHIP and CtBP2 to the pathogenesis of human breast cancer has never been addressed, but our present study implies that the elevated CtBP2 observed in human breast cancer [12] may be due to inefficient regulation caused by low levels of CHIP protein and may contribute to the anti-apoptotic property of human breast cancer by repressing pro-apoptotic gene expression.…”
Section: Regulation Of Ctbp2 By Chip Affects the Expression Of Ctbp2 mentioning
confidence: 53%
“…CtBP2 was recognized as an oncogenic protein that represses pro-apoptotic genes, and elevated CtBP2 is implicated in various human cancers including breast cancer [12][13][14], suggesting that maintaining a proper level of CtBP2 is crucial for preventing tumorization. Our study provides the first evidence that CHIP as an E3 ubiquitin ligase negatively regulates CtBP2 in a ubiquitin-proteasome-dependent manner.…”
Section: Regulation Of Ctbp2 By Chip Affects the Expression Of Ctbp2 mentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of the protein variants with potential cancer relevance is shown in Table 1. The isoforms of the NADH-binding transcriptional repressor CtBP1 are important regulators of tumor suppressors (61) that are required for high-fidelity replication of DNA during mitosis (38,62) and play a role in breast cancer chemoresistance (63). Isoform 2 of CtBP1 was down-regulated by PCB and, to a lesser extent, by Pht in organoids treated with these chemicals.…”
Section: Functional Classes Of Proteins and Pathways Changed By Exposmentioning
confidence: 98%
“…The CTBP1 gene encodes for a phosphoprotein that acts in the nucleus as a transcriptional repressor and in the cytoplasm in the maintenance of vesicular membranes [55]. CTBP1 degradation on colon cancer depends on the tumor suppressor adenomatous polyposis coli (APC); when this protein is mutated, CTBP1 increased resulting in the initiation of the adenoma formation [56].…”
Section: Other Combinations Based On 5-fumentioning
confidence: 99%